PEMANFAATAN JELUTUNG (Dyera spp.) OLEH SUKU ANAK DALAM DI TAMAN NASIONAL BUKIT DUABELAS , JAMBI - ., Aminah; Zuhud, Ervizal A.M.; Siregar, Iskandar Z. (Media Konservasi, 2016)
Anak Dalam Tribe (Suku Anak Dalam; SAD) used jelutong in their daily live. But nowadays, jelutong population was reduced. Increase the forest change area decrease the habitat preference of jelutong. It need the strategy and technique to conservation jelutong without conflict with local people interest. Traditional management of jelutong among SAD in Bukit Duabelas National Park (Taman Nasional Bukit Duabelas; TNBD) benefits to understanding technique used of jelutong latex and understanding ecological knowledge SAD for strategy of conservation jelutong, among  other are to described  jelutong population status in TNBD. The research was conducted by using focus group discussion and indepth interview 40 respondent to examine management and use of jelutong. In addition, vegetation analysis was also conducted to determine the status of jelutong population by 8 sampling plots with census technique in 2,88 ha area. It was determined that SAD use latex of jelutong especially for comodity. Traditional technique applied to all methods tapping, production, and marketing latex. Time latex tapping done in early morning on 5 to 6 am because sunrise decreased latex production. Latex mixed with samak (Syzygium pyrifolium) or vinegar 61, allowed to stand until thickened and forming lumps fit the mold. The local management of this species is based on simple maintenance and tapping latex of individuals in the swamp area, dryland area and homegardens agroforest.The structure of jelutong population in TNBD was destructed which are distribution number of jelutong per ha young stage less than mature stage. Keywords: Anak Dalam Tribe, bioprospecting, conservation, Dyera spp., ethnobotany